Questions: Complete the table of values for f(x)=2(4)^x and g(x)=8x+6. x, f(x), g(x) 0, square, square 1, square, square 2, square, square 3, square, square Both f(x) and g(x) grow as x gets larger and larger. Which function eventually exceeds the other? f(x)=2(4)^x g(x)=8x+6

Complete the table of values for f(x)=2(4)^x and g(x)=8x+6.

x, f(x), g(x)
0, square, square
1, square, square
2, square, square
3, square, square

Both f(x) and g(x) grow as x gets larger and larger. Which function eventually exceeds the other?
f(x)=2(4)^x
g(x)=8x+6
Transcript text: Complete the table of values for $f(x)=2(4)^{x}$ and $g(x)=8 x+6$. \begin{tabular}{|c|l|l|} \hline $\boldsymbol{x}$ & $\boldsymbol{f ( x )}$ & $\boldsymbol{g ( x )}$ \\ \hline $\mathbf{0}$ & $\square$ & $\square$ \\ \hline 1 & $\square$ & $\square$ \\ \hline 2 & $\square$ & $\square$ \\ \hline 3 & $\square$ & $\square$ \\ \hline \end{tabular} Both $f(x)$ and $g(x)$ grow as $x$ gets larger and larger. Which function eventually exceeds the other? $f(x)=2(4)^{x}$ $g(x)=8 x+6$ Submit Work it out
failed

Solution

failed
failed

Solution Steps

Step 1: Calculate \( f(x) \) and \( g(x) \) for \( x = 0 \)

For \( x = 0 \):

  • \( f(0) = 2(4)^0 = 2 \times 1 = 2 \)
  • \( g(0) = 8(0) + 6 = 0 + 6 = 6 \)
Step 2: Calculate \( f(x) \) and \( g(x) \) for \( x = 1 \)

For \( x = 1 \):

  • \( f(1) = 2(4)^1 = 2 \times 4 = 8 \)
  • \( g(1) = 8(1) + 6 = 8 + 6 = 14 \)
Step 3: Calculate \( f(x) \) and \( g(x) \) for \( x = 2 \)

For \( x = 2 \):

  • \( f(2) = 2(4)^2 = 2 \times 16 = 32 \)
  • \( g(2) = 8(2) + 6 = 16 + 6 = 22 \)
Step 4: Calculate \( f(x) \) and \( g(x) \) for \( x = 3 \)

For \( x = 3 \):

  • \( f(3) = 2(4)^3 = 2 \times 64 = 128 \)
  • \( g(3) = 8(3) + 6 = 24 + 6 = 30 \)
Step 5: Complete the Table

The completed table is as follows:

\[ \begin{tabular}{|c|l|l|} \hline \(\boldsymbol{x}\) & \(\boldsymbol{f(x)}\) & \(\boldsymbol{g(x)}\) \\ \hline \(\mathbf{0}\) & 2 & 6 \\ \hline 1 & 8 & 14 \\ \hline 2 & 32 & 22 \\ \hline 3 & 128 & 30 \\ \hline \end{tabular} \]

Step 6: Determine Which Function Eventually Exceeds the Other

As \( x \) increases, \( f(x) = 2(4)^x \) grows exponentially, while \( g(x) = 8x + 6 \) grows linearly. Exponential functions grow faster than linear functions, so \( f(x) \) will eventually exceed \( g(x) \).

Final Answer

The completed table is:

\[ \boxed{ \begin{tabular}{|c|l|l|} \hline \(\boldsymbol{x}\) & \(\boldsymbol{f(x)}\) & \(\boldsymbol{g(x)}\) \\ \hline \(\mathbf{0}\) & 2 & 6 \\ \hline 1 & 8 & 14 \\ \hline 2 & 32 & 22 \\ \hline 3 & 128 & 30 \\ \hline \end{tabular} } \]

The function \( f(x) = 2(4)^x \) eventually exceeds \( g(x) = 8x + 6 \).

\[ \boxed{f(x) \text{ eventually exceeds } g(x)} \]

Was this solution helpful?
failed
Unhelpful
failed
Helpful